Perubahan Paradigma Pendidikan Melalui Pemanfaatan Teknologi di Era Global - Dianis Svari, Ni Made Fanny; Arlinayanti, Kadek Dwi (Jayapangus Press, 2024)
The government has the main goal of managing the education system to produce quality citizens who are ready to face the dynamics of globalization. The importance of intelligence for each individual is crucial in facing the ongoing era of globalization. Education in the era of globalization can be understood as an effort to integrate the national education system into a broader global education context. The ever-growing development of technology has entered the digital era, where every sector, including education, has switched to using technology to simplify work and teaching processes. In the educational context, educational technology is an important foundation in supporting the learning process to achieve the desired goals. The aim of this research is to determine changes in the educational paradigm through the use of technology in the global era. This research uses qualitative methods with literature study. The data analysis technique in this research was carried out descriptively based on research results obtained through observation, interviews and documentation. The research results show that the role of technology in the world of education is very diverse, including the use of various learning media, administrative tools, and learning resources that can be accessed digitally. The implementation of technology in education has positive impacts, such as increasing efficiency in managing time, costs and logistics, as well as solving various existing institutional problems. However, it cannot be denied that technological advances also have significant social impacts, which need to be considered carefully so that they do not lead to undesirable changes in the social structure of society. Therefore, while technology provides great benefits in the world of education, it is also important to monitor its impact carefully to ensure that social interests are also maintained.